2005
DOI: 10.1002/pmic.200401147
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic investigation into etoposide chemo‐resistance of neuroblastoma cell lines

Abstract: Neuroblastoma, one of the most common pediatric solid tumors, originates from the peripheral sympathetic nervous system and is responsible for approximately 15% of all childhood cancer deaths. Among the several antineoplastic drugs used in neuroblastoma chemotherapeutic protocols, topoisomerase inhibitors (i.e., etoposide) represent the most commonly used. Several resistance mechanisms limit the clinical success of topoisomerase-targeting drugs, mainly reducing the ability of neoplastic cells to start programm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 35 publications
3
30
0
1
Order By: Relevance
“…Overexpression of vimentin has been observed in various epithelial cancers and correlated with accelerated tumor growth, invasion, and poor prognosis (50). Furthermore, etoposide resistance in neuroblastoma cell and vinca alkaloid resistance in acute lymphoblastic leukemia have been linked to overexpression of vimentin (51)(52). However, down-regulation of vimentin has been found in resistant1A9 cells to the microtubule stabilizing agents, PLA and LAU (53), consistent with results from the present study.…”
Section: Discussionsupporting
confidence: 81%
“…Overexpression of vimentin has been observed in various epithelial cancers and correlated with accelerated tumor growth, invasion, and poor prognosis (50). Furthermore, etoposide resistance in neuroblastoma cell and vinca alkaloid resistance in acute lymphoblastic leukemia have been linked to overexpression of vimentin (51)(52). However, down-regulation of vimentin has been found in resistant1A9 cells to the microtubule stabilizing agents, PLA and LAU (53), consistent with results from the present study.…”
Section: Discussionsupporting
confidence: 81%
“…According to it, we saw that the neural markers SgII and NEF-L and the proliferating marker PCNA were differentially regulated by RA in the SH-SY5Y and SK-N-BE cell lines as compared to the LAN-5 cell line. In the three cell lines, we also observed the PRDX2 protein up-regulation which has been seen in the SH-SY5Y cell line upon treatment with the anti-neoplastic drug ectoposide 22 and during differentiation of embryonic stem cells to neural cells by ATRA. 29 Moreover, we observed that the ATRA treatment down-regulates the EF1R and EF-2 proteins, and this effect has just been reported in promyelocitic cells.…”
Section: J Journal Of Proteome Researchmentioning
confidence: 63%
“…The most commonly used comparative proteomic approach is two-dimensional difference gel electrophoresis (2D-DIGE) coupled with mass spectrometry (MS), which provides a good proteomic tool for the investigation of novel proteins that might serve as candidates for tumor markers. Previously, 2D-PAGE analyses of protein changes were performed to study chemoresistance, 22 to search for markers for tumor diagnosis in NB cell lines, 23,24 and to study quantitatively and qualitatively differences in healthy and pathological NB mouse samples. 25,26 Moreover, proteomic characterization of differentiation induced by ATRA has been described in promyelocytic cells 7,27,28 and in mouse embryonic stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced expression of this hnRNP is not restricted to CML-BC, as HNRPK overexpression has also been associated with tumor progression and resistance to therapeutic drug-induced apoptosis in different types of cancer. [34][35][36][37] By assessing the mechanism whereby BCR/ABL augments HNRPK levels, we found that Hnrpk mRNA expression depends on the BCR/ABL-regulated activity of MAPK ERK1/2 . In fact, BCR/ABL-graded expression activates MAPK ERK1/2 and increases HNRPK levels in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%